Modulating electrolyte solvation structures with Fe-embedded carbon matrix substrates for robust lithium-metal plating - Peng, Jiayue; Wang, Jinghan; Pu, Xiangjun; Xie, Jia (Journal of materials chemistry. A, Materials for energy and sustainability, 2025)
The practical application of lithium metal as an anode faces challenges due to the uncontrolled growth of lithium dendrites and substantial volume expansion. In this study, we synthesized a porous Fe@C material through the pyrolysis of Fe-based metal-organic frameworks (MOFs), showcasing its efficacy as a substrate for lithium plating. Increased anion participation occurs in the Li + solvation sheath within the Fe@C pores, leading to the formation of an anion-derived solid electrolyte interface (SEI). The Fe matrix serves as nucleation sites, and the pores optimize the electrolyte structure, effectively guiding Li deposition while inhibiting Li dendrite formation. This approach demonstrates outstanding electrochemical performance with extended cycling, presenting a promising strategy for stable lithium metal anodes. Carbonized Fe-BTC to Fe@C is utilized as a substrate to enhance lithium deposition by modulating the Li + solvation structure. This approach significantly improves cycling performance.